Gunst/Ungunst (Tübingen University Press, 2024)
On October 28 and 29, 2016, representatives of prehistoric and early historical archaeology, archaeobotany, classical archaeology, physical geography/soil science, human geography, ethnology and history met at Tübingen Castle to enter into an interdisciplinary dialog on "Favour/unfavour - use and perception of (marginal) spaces". Together, older research concepts were critically scrutinized and new approaches to researching the socio-cultural perception of spaces and resources were discussed. It was found that studies on favor and disfavor have until recently been dominated by natural determinist concepts, in which nationalist and colonialist narratives of conquest from the 19th century continue to have an effect. Of outstanding importance for the turnaround towards a differentiated debate and the further development of outdated possibilistic concepts are therefore not only critical reflections on the reciprocal influence of research and zeitgeist, but also interdisciplinary initiatives in which old paradigms are questioned and new paths are taken.